Pengaruh Komunikasi Terhadap Produktivitas Kerja Pegawai Pada Puskesmas Pseksu Kabupaten Lahat - Rustam Efendi (Jurnal Manajemen dan Bisnis, 2020)
The aim of this study is to determine the effect of communication on the productivity of employees working at PSEKSU Lahat and to determine the relationship of communication with employee productivity in PSEKSU Lahat. This form of research is the analysis of qualitative and quantitative analysis. The sample in this study is an employee at the health center Lahat PSEKSU totaling 30 employees. Because the number of employees at the health center PSEKSU as many as 30 people, then the sample is taken from the total population. So the sampling technique in this study using census method of data collection for the entire population. Data collection techniques in this research is through observation, interviews, and distribution of a list of questions to the respondent and methods used in this research is the method of qualitative analysis and quantitative analysis method with a simple formula of linear regression, correlation coefficient, coefficient terminated and hypothesis t test. Of regression and correlation calculations obtained simple linear regression equation is Y = 7.37 + 0.74 X +e . These values ​​have meaning if the communication variables is increased one unit then the employee productivity will be increased by the value of b is 0.74. From the calculation results obtained r = 0.83 means a correlation coefficient of 0.83. This means of communication has a positive relationship and a very closely to employee productivity. Coefficient calculation known determinant of the value of KD = 0.69 or 69% means that employee productivity is affected by the communication by 69% and the remaining 31% are influenced by other factors such as leadership, incentives, division of tasks and training. From the hypothesis testing calculation obtained value t count = 7.896 and t-table 2, 048. So t-count value is greater than t-table or t count> t table, this shows that Ho is rejected, which means there is a significant relationship between communication to work productivity of employees at the health center PSEKSU Lahat. The calculation can be interpreted that Ho is rejected and Ha accepted then the hypothesis is proven and showed a significant correlation means of communication have a positive effect on employee productivity in PSEKSU Lahat.